ANALIS1S INVESTASI RENCANA PENAMBANGAN ASBUTON DI BLOK I BATUAWU - LAPANGAN LAWELE, KABUPATEN BUTON, PROPINSI - SULAWESI TENGGARA - Virtani Anas (NIM : 221 96009), Aryanti
Abstract : The activities of asbuton mining at block I Batuawu, Lawele Field are planned to start in 1998. The mining system is surface mining with open pit mining method. The amount of measured reserves is 5,710,000 tons, mineable reserves is 5,424,000 tons (mining recovery is 95 %), and mining production target will be 568,421 tons/year for 10 years. As we know, mining investment industry is one of the high-risk investments, particularly within economic crisis like this time. Therefore, it is necessary to calculate the criteria of investment evaluation, and the investment benefits. Asbuton mining investment analysis uses the engineering economic analysis that is based on the data of cost estimate, revenue estimate, and the other economic variables such as inflation rate, interest rate, and taxes. The investment analysis involves financial analysis and benefit analysis, and carried out to calculate whether the investment will be profitable or not. The financial analysis consists of cash flow analysis, static analysis, sensitivity analysis, and policy evaluation using three exchange rates, namely Rp. 10,000, Rp. 11,000, and Rp. 12,000. Cash flow analysis uses three depreciation methods: (i) straight line,ii) sum of the years digit, and (iii) double declining balance, whereas static analysis uses straight line depreciation method. Sensitivity analysis is applied to calculate the investment sensitivity against the changes of price, capital investment cost, non-capital investment cost, production cost, and exchange rate. Policy evaluation is applied to evaluate the government policies that may influence investment values such as income tax, and interest rate. The benefit analysis is applied to know the social and economic benefits of asbuton mining. There are some benefits that can be obtained from this investment: (i) the economy of country\'s foreign exchange, (ii) the increasing of government\'s income, and iii) the enlargement of work opportunity. The analysis results show that asbuton mining investment at block I Batuawu will be profitable, although the investment is recommended to be postponed until the economy of Indonesia will change to the better.